Case Report: A Case of Glioblastoma in a Patient With Haberland Syndrome - Ferranti, Silvia; Sardi, Iacopo; Guidi, Milena; Lembo, Chiara; Grosso, Salvatore (Frontiers in Pediatrics, 2021)
Haberland syndrome or encephalocraniocutaneous lipomatosis is a rare ectomesodermal dysgenesis defined by the triad including ocular, skin, and central nervous system involvement, which is commonly unilateral. This disorder is attributed to a post-zygotic mutation responsible for a neural tube and neural crest dysgenesis. We report the case of a 15-year-old female with Haberland syndrome with pharmacoresistant epilepsy who developed a World Health Organization-grade IV glioblastoma. This is the first case of pediatric glioblastoma associated with Haberland syndrome. The previously reported pediatric cases included benign brain tumors. To our knowledge, this is the fifth case of brain tumor associated with encephalocraniocutaneous lipomatosis and the second case of glioblastoma associated with this syndrome. The hypothesis that Haberland syndrome is associated with an increased risk of tumor development is intriguing, although the rarity of the condition is nowadays preventing us from drawing definitive conclusions about this potential link between the two entities. Further studies are needed to establish the real relationship between encephalocraniocutaneous lipomatosis and the risk of brain tumors.